The Potential Effect of Novel Coronavirus SARS-CoV-2 on NK Cells; A Perspective on Potential Therapeutic Interventions - Jewett, Anahid (Frontiers in Immunology, 2020)
Coronavirus-induced disease-2019 (COVID-19) continues to cause significant morbidity and mortality worldwide. While studies on SARS-CoV-2 effects on immune cell function continue to progress, we know very little about the significance of depletion of key immune effectors by the virus in the mortality and morbidity of the disease. This commentary outlines what is known about the effect of virus on NK cells known to kill virally infected cells. It also underscores the necessity of future comprehensive studies of NK cells in SARS-CoV-2 infected individuals and animal models to better understand the role and significance of reported NK depletion and functional inactivation in disease morbidity and mortality, in hope to design effective therapeutic interventions for the disease.